Programme-135: Addressing poverty and inequality in Viet Nam - Tung Duc Phung; Thanh Minh Pham (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
Viet Nam has achieved remarkable economic growth and poverty reduction since the Doi Moi. However, ethnic minorities and the ethnic majority do not benefit equally from the national economic progress. The proportion of poor households that are ethnic minority-headed soared from 18 per cent in the early 1990s to 56 per cent in 2008. The disparity exists in their access to crucial basic infrastructure and public services, including transportation, education, healthcare, electricity supply, markets, and justice services. Initiated in 1998, Programme-135 targets the most vulnerable communities and aims to promote production, increase access to basic facilities, improve education, and raise awareness for better living standards. The programme addresses typical causes of poverty among ethnic minorities and inequality between these groups and the majority. Programme-135 has created positive impacts and successfully improved the lives of the beneficiaries. In this paper we provide an overview of the programme and examine the drivers of its success in reducing poverty and bridging the majority-minority development gap. We also discuss the limitations and lessons from the programme.
Keywords: I38; J15; J18; 330; poverty reduction; inequality; ethnic minorities; Viet Nam